Most Black women have a regular source of hair care--but not medical care. - Browne, Ruth C. (National Medical Association, 2006)
In this issue, Brown, Naman, Homel et al. present the results of an innovative community-based health education program that the Arthur Ashe Institute for Urban Health has conducted in African-American beauty salons since 1996. Black Pearls: The Health and Beauty of the Black Woman is a beauty-salon-based health education and screening program in Brooklyn, NY that has recently been replicated in West Philadelphia, PA.